Reentry in Practice: Sexual Offending, Self-Narratives, and the Implications of Stigma in Norway - Sandbukt, Ingeborg Jenssen (International journal of offender therapy and comparative criminology, 2023)
Reentering society after serving a prison sentence involves many challenges and particularly so for one of the most stigmatized groups in modern society: people who have sexually offended. While most research on their reentry has been conducted in countries with Sex Offender Registration and Notification (SORN) laws, this study used Interpretative Phenomenological Analysis (IPA) to qualitatively investigate the accounts and experiences of men released from prison after serving a sex offense conviction in Norway (n = 8). Results showed that despite less restrictive policies and a total absence of SORN laws, the social stigma linked to being convicted of such crimes severely affected the men. To some degree, they all experienced feelings of stress or anxiousness and they withdrew and isolated more. Their narratives highlight a need for increased social support and recognition from others in the reentry process. Subjective and societal consequences as well as practical implications are discussed.